DEVELOPMENT OF STEM-BASED E-LKPD IN THE SUBJECT OF AQIDAH AND AKHLAK TO IMPROVE STUDENT LEARNING OUTCOMES - Rabba Yenni Pardosi; Munawir Pasaribu; Robie Fanreza (RADJA PUBLIKA, 2026)
This research aims to develop and test the effectiveness of STEM-based E-LKPD on Commendable Morals material for grade XI students of MAN Dairi. The research uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of two classes: class XI Science 2 as an experimental class and class XI Science 3 as a control class. Data was collected through tests and questionnaires, then analyzed using validity, reliability, and Independent-Samples T-Test tests with the help of SPSS 26. The results showed that STEM-based E-LKPD obtained an average validity value of 94.9% with the